USALI 12 and The Evolution of Hotel Operational Reporting - Christina Susanti; I.G.N.A Wiryanata; D.A. Rai Sumariati (Asian Journal of Management Analytics, 2026)
This study examines the evolution of hotel operational reporting under the Uniform System of Accounts for the Lodging Industry (USALI) 12th Revised Edition. Using a descriptive qualitative approach and content analysis of official USALI 12 documents and related literature, the study highlights key revisions, including Executive Lounge reporting, Guest Loyalty Program cost classification, enhanced Sales and Marketing accounts, sustainability-related schedules (energy, water, and waste), Full-Time Equivalent, mandatory brand costs, and all-inclusive hotel reporting. Findings indicate that USALI 12 improves reporting transparency, cost classification, labour and resource measurement, and performance standardisation, while aligning hotel reporting practices with current operational and sustainability demands.